Association between weight-adjusted waist circumference index and risk of cognitive decline in Chinese hypertensive patients: a case-control study - Zhang, Mengdi; Liu, Donghai; Yan, Xipeng; Niu, Zhenchao; Zhang, Yudong; He, Lei; Jiao, Huachen (Frontiers in Public Health, 2025)
BackgroundAs a new obesity-related index, the weight-adjusted waist circumference index (WWI) seems to be a good predictor of cognitive decline in hypertensive patients. This study aimed to verify the relationship between WWI and cognitive decline in Chinese hypertensive patients.MethodsData were obtained from the Hypertension Follow-up System of Shandong Province. WWI was calculated by dividing waist circumference by the square root of body weight, and cognitive decline was judged based on Mini-Mental State Examination (MMSE) scale scores. Multivariate logistic regression models and subgroup analyses were used to assess the relationship between WWI and cognitive decline in hypertensive patients.ResultsA total of 2,204 participants were included. There was a positive association between WWI and cognitive decline in hypertension (HCD). After adjusting for all covariates, a one-unit increase in WWI was associated with a 12% increase in the risk of cognitive decline in hypertensive patients (OR: 1.12, 95%CI: 1.04–1.21). In addition, the multivariable-adjusted OR for the highest quartile (11.16–16.76) compared with the lowest quartile of WWI (7.00–10.11) was 1.61 (95% CI: 1.30–2.00).ConclusionIn Chinese hypertensive patients, high levels of WWI were significantly associated with an increased risk of cognitive decline. This finding suggests that WWI may be an indicator of the risk of cognitive decline affecting hypertensive patients.